THE INTEGRATION OF CORPUS INTO EFL SPEAKING INSTRUCTION: A STUDY OF LEARNER PERCEPTIONS - Kızıl, Aysel Şahin; İtik, Zehra (My University, 2018)
Recent years have shown a growing interest in using corpora in language instruction,enhancing data-driven learning (DDL) pedagogy by promoting the use of tools andtechniques of corpus linguistics in language classrooms. Many studies have tested the impactof corpus tools in EFL writing or vocabulary instruction; however, little attention has beenpaid to the integration of corpus tools into EFL speaking instruction. This paper describes asmall-scale study of corpus use in enhancing English speaking performance of EFL learnerswith a focus on their perceptions towards web-based concordancing. Drawn in accordancewith convenience sampling procedures, the participants of the study were 31 university levelEFL learners who experienced DDL activities in the speaking classroom. Data collectedthrough a post-instruction perception questionnaire were analysed using descriptive statistics.Results indicatethat students benefited from concordance-based learning activities, and alsohold positive attitudes towards using it in learning speaking. The findings also point out somechallenges to overcome while using web-based concordancing in EFL instruction.
Keywords: Eğitim; Eğitim Araştırmaları